Sex-specific relationship of cardiometabolic syndrome with lower cortical thickness - Kim, Si Eun (Neurology, 2019)
OBJECTIVE: To investigate whether cardiometabolic factors were associated with age-related differences in cortical thickness in relation to sex. METHODS: In this cross-sectional study, we enrolled 1,322 cognitively normal elderly (≥65 years old) individuals (774 [58.5%] men, 548 [41.5%] women). We measured cortical thickness using a surface-based analysis. We analyzed the associations of cardiometabolic risk factors with cortical thickness using multivariate linear regression models after adjusting for possible confounders and interactions with age. RESULT: Among women, hypertension (β = −1.119 to −0.024, p < 0.05) and diabetes mellitus (β = −0.920, p = 0.03) were independently associated with lower mean cortical thickness. In addition, there was an interaction effect between obesity (body mass index [BMI] ≥27.5 kg/m(2)) and age on cortical thickness in women (β = −0.324 to −0.010, p < 0.05), suggesting that age-related differences in cortical thickness were more prominent in obese women compared to women with normal weight. Moreover, low education level (<6 years) was correlated with lower mean cortical thickness (β = −0.053 to −0.046, p < 0.05). Conversely, among men, only being underweight (BMI ≤18.5 kg/m(2), β = −2.656 to −0.073, p < 0.05) was associated with lower cortical thickness. CONCLUSIONS: Our findings suggest that cortical thickness is more vulnerable to cardiometabolic risk factors in women than in men. Therefore, sex-specific prevention strategies may be needed to protect against accelerated brain aging.